Steady-State Pharmacokinetics of Oral Ciprofloxacin in Continuous Cycling Peritoneal Dialysis Patients: Brief Report. Issue 1 (January 2018) - Lee, Colin; Walker, Sandra A.N.; Palmay, Lesley; Walker, Scott E.; Tobe, Sheldon; Simor, Andrew
Steady-state pharmacokinetics of oral ciprofloxacin in 3 continuous cycling peritoneal dialysis (CCPD) outpatients given ciprofloxacin 750 mg b.i.d. for 5 doses was determined. Mean steady-state maximum serum concentration and half-life were 4.4 ±1.5 mg/L and 10.3 ± 2.6 hours, respectively. Mean maximum dialysate concentration in the daytime long dwell and overnight continuous cycling dwell were 7.4 ± 1.2 mg/L and 3.3 ± 1.2 mg/L, respectively. Oral ciprofloxacin 750 mg b.i.d. may be reasonable for bloodstream and peritoneal infections caused by susceptible bacteria in CCPD patients.